IMPLEMENTASI LITERASI BUDAYA DAN KEWARGAAN PADA PEMBELAJARAN PLBJ DI SDN KAPUK 06 PAGI - Ruwanda, Nabila Dinda; Andriana, Encep; Rahmani, Anggi (Universitas Islam 45 Bekasi, 2025)
This study aims to describe the implementation of cultural and civic literacy in the teaching of Pendidikan Lingkungan Budaya Jakarta (PLBJ) at SDN Kapuk 06 Pagi. A descriptive qualitative approach was employed, utilizing data collection techniques such as observation, interviews, and documentation. The findings indicate that lesson planning was carried out contextually, integrating cultural and civic values into each designed component. The learning process was conducted actively and meaningfully, applying a scientific approach and the Problem-Based Learning model, which involved simple projects and activities based on local culture. The results of this implementation show that students have begun to understand Betawi culture as a local identity and have demonstrated tolerant attitudes as well as concern for their social environment. Supporting factors include teacher preparedness, support from the school principal, and adequate facilities and infrastructure. Conversely, challenges encountered include limited culture-based learning media and uneven student interest in cultural subjects. This study concludes that PLBJ instruction plays a role in gradually fostering cultural and civic literacy through activities relevant to students’ lives in a multicultural environment.